Increased enzymatic activity of the alternative pathway convertase when bound to the erythrocytes of paroxysmal nocturnal hemoglobinuria. - Parker, C J (1982)
To investigate the greater fixation of C3 to the erythrocytes of patients with paroxysmal nocturnal hemoglobinuria (PNH) upon activation of complement, we have examined the formation and the reaction of the C3 nephritic factor-stabilized alternative pathway convertase made with purified components on normal and PNH erythrocytes. Each convertase complex converts four to five times more fluid-phase C3 to C3b when affixed to a PNH cell than when affixed to a normal cell. The greater activity of the convertase on PNH cells is not due to differences in the intrinsic or extrinsic stability of the convertase complex. The excessive binding of C3 to PNH cell si due to this increased conversion of fluid-phase C3, because the efficiency of binding of nascent C3b was identical for the two cell types. This is the first instance in which the enzyme activity of a complement complex has been shown to be increased by being affixed to an abnormal surface.